Principles Of Cell Biology - George Plopper (Jones & Bartlett Learning, 2013)
very new copy of Principles of Cell Biology includes access to the Student Companion Website Written for the undergraduate Cell Biology course, Principles of Cell Biology provides students with an accessible approach to the fundamental concepts of cell biology. With a concept-based approach, the text focuses on the underlying principles that illustrate both how cells function as well as how we study them. It identifies 10 specific principles of Cell Biology, and devotes a separate chapter to illustrate each. The result is a shift away from the traditional focus on technical details and towards a more integrative view of cellular activity that is flexible and can be tailored to suit students with a broad range of backgrounds. An informal, narrative writing style makes even the most complex concepts accessible to students new to the scientific field, including eliminating much of the technical complexity that many students find intimidating. With a wealth of student and instructor ancillary items to round out the course Principles of Cell Biology is the clear choice for your students.